Urgensi Pembelajaran Akidah Islam Dalam Membentuk Karakter Religius Siswa - Sabrina Salsabilla Ali; Muhammad Imamul Muttaqin (Al'Adalah, 2022)
Studying the Islamic faith (aqedah) in today's era is very important. The flow of globalization is full of freedom in our daily life and can bring us positive or negative effects without realizing it. The thing that is most feared is if the impact of globalization has a bad influence on us, especially on students who are still looking for their own identity. The weakness of faith can cause this negative influence as the foundation of one's faith. If a student's faith is weak, he will be easily influenced or provoked by the circumstances around him, easily swayed by what he previously believed. In this article, we will examine three interrelated questions. First, what is the meaning of the Islamic creed, and what is its position in our lives? Second, what is the meaning of religious character? Third, how is the urgency of learning creed in shaping the religious character of students? This article uses a library research approach to review the three points above. The result is that strengthening faith through learning the Islamic faith will be very much needed as an effort to prevent negative things from entering students. In addition, the Islamic faith can also be said to reflect their character.